2021
DOI: 10.3390/foods10123062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radio Frequency Pretreatment on Quality of Tree Peony Seed Oils: Process Optimization and Comparison with Microwave and Roasting

Abstract: In this study, we explored the technical parameters of tree peony seeds oil (TPSO) after their treatment with radio frequency (RF) at 0 °C–140 °C, and compared the results with microwave (MW) and roasted (RT) pretreatment in terms of their physicochemical properties, bioactivity (fatty acid tocopherols and phytosterols), volatile compounds and antioxidant activity of TPSO. RF (140 °C) pretreatment can effectively destroy the cell structure, substantially increasing oil yield by 15.23%. Tocopherols and phytoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
(63 reference statements)
2
8
1
Order By: Relevance
“…As a result, the RF treatment had effected the AV of peanut oil at the selected electrode height and conveyor speed which interpreted that exposing to high‐temperature RF heating causes oxidation and acidification in the oils (Liao et al, 2018). A similar observation was recorded by Wang et al (2021) where RF treatment showed an increase in AV of peony seed oils. RF roasting of salted peanuts also increased the AV of peanut oils (Jiao et al, 2016).…”
Section: Resultssupporting
confidence: 89%
“…As a result, the RF treatment had effected the AV of peanut oil at the selected electrode height and conveyor speed which interpreted that exposing to high‐temperature RF heating causes oxidation and acidification in the oils (Liao et al, 2018). A similar observation was recorded by Wang et al (2021) where RF treatment showed an increase in AV of peony seed oils. RF roasting of salted peanuts also increased the AV of peanut oils (Jiao et al, 2016).…”
Section: Resultssupporting
confidence: 89%
“…However, in another traditional vegetable oil, the content of sesame oil (SESO) was slightly lower than that of other results, which might be attributed to different sesame cultivars ( Rodríguez et al, 2020 ). Compared with conventional oil crops, most of novel oilseed crops were abundant with unsaturated fatty acids, and the unsaturated fatty acids content of PKSO, HSO, PLSO and PNSO exceeded 81 g/100 g, similar to former reports ( Tura et al, 2022 , X. Wang et al, 2021 , Z. Wang et al, 2021 ). The relatively higher MUFA contents were demonstrated from three woody oils, oil-tea oil (OSO), palm oil (PO), and olive oil (OO).…”
Section: Resultssupporting
confidence: 87%
“…The relatively higher MUFA contents were demonstrated from three woody oils, oil-tea oil (OSO), palm oil (PO), and olive oil (OO). The levels of oleic acid, the major MUFA in OSO and OO, were 64.53 and 50.24 g/100 g, lower than former reports, 76.18% and 72.77%, respectively ( Guo et al, 2017 , Liu et al, 2021 , Z. Wang et al, 2021 , Suealek et al, 2021 ). The oleic acid in PO was 56.26 g/100 g which was in agreement with a crude palm oil study ranging from 47.4% to 53.5% ( Morcillo et al, 2021 ).…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…Nevertheless, there were differences in the types, and the contents of aldehydes, ketones and esters were also increased. After enzymatic hydrolysis, MR eliminated the unpleasant smell of oyster, and a pleasant smell of milk, nut and meat was generated at the same time ( 48 ).…”
Section: Flavor Ingredients Of Mrps and Detection Methodsmentioning
confidence: 99%